Evaluation of Dynamic Pulmonary Function in Obese Individuals (TAJ: Journal of Teachers Association, 2018)
Introduction: Obesity is becoming a major health hazard in developed and developing countries. Besides the well-known complication like Diabetes mellitus, hypertension. ischemic heart disease, obesity can affect thorax, diaphragm, abdominal muscles, thereby resulting in altered pulmonary functions.Objective: To evaluate the effects of obesity on lung functionsMethods: We studied 208 adults of both sex with the age range of 18 to 60. 104 obese subjects were taken as test group (BMI ≥ 25 Kg/m2) & 104 non obese individuals (BMT 18.5-24.9 Kg/m2) as control group. Spirometry was performed by using computerized spirometer. Data were expressed as mean & standard deviations. Data were analysed by the help of SPSS version-16. non pair student’s ‘t’ test (P values ≤ .05 were considered significant) Pearson correlation analysis & multiple linear regression tests were applied.Results: FVC% (mean & standard deviation), in obese group (Group A) and non obese group (Group B) were 73.42±8.24, 84.05±5.94 respectively. FEV1% (mean & standard deviation), in obese group (Group A) and non obese group (Group B) were 74.65±7.29. 84.22±5.95 respectively. FEV1/FVC% (mean & standard deviation), in obese group (Group A) and non obese group (Group B) were 101.30±9.87, 99.57±11.50 respectively. PEF% (mean & standard deviation), in obese group (Group A) and non obese group (Group B) were 65.98±14.21. 93.53±13.21 respectively. There are statistically significant differences of spirometry results in absolute values and in percentage predicted between two groups, except FEV1/FVC. There were also significant negative correlation between obesity indices (BMI. WC) and spirometric variables except FEV1/FVC%.Conclusion: Obesity independently affects pulmonary functions.TAJ 2014; 27(2): 14-21